FUNGSI BUAH DAN DAUN TANAMAN DALAM BUDAYA BALI SEBUAH KAJIAN TERHADAP TANAMAN UPACARA - I Nyoman Adiputra (Bumi Lestari Journal of Environment, 2017)
According to the Balinese culture, there are some classifications of plants, such as: medicinal plants, ceremonial plants, commodity plants, horticulture, and magical plants. Due to it’ very importance value, culturally, there is a special day for the existing plants, called tumpek uduh, where a special offering is intended to the god of plantation. In this article is drawn function of leaves and fruits as a material for offering. Analysis is focused on the use of fruits as pala gantung, pala bungkah or tuber for the offerings to the god. The leaves are used for religious ceremony in term of panca dhala or asta dala. In composing the offerings, there is a guidance derived from tatwa pangider-ideran (point of compass). The used of leaves and fruits, is based on the color of leaves and fruits. The goals are for preserving/ conserving and peace-full fitting of nature. The liquid of young coconut fruits are used for the process of purifications materials, places, and the symbols of religious matters. Starting from east direction: nyuh bulan, east-south: nyuh rangda, south direction: nyuh udang, south west: nyuh surya, west direction: nyuh kuning, west-north: nyuh be julit, north direction: nyuh mulung, and the middle: nyuh sudamala. That is the respective-, dedicative offerings from human being to the nature by making use of materials for the feacefull, safety, and sustainability of the nature itself.